2018
DOI: 10.1016/j.ijmultiphaseflow.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of stratified two-phase channel flows of Newtonian/non-Newtonian shear-thinning fluids

Abstract: Linear stability of horizontal and inclined stratified channel flows of Newtonian/non-Newtonian shearthinning fluids is investigated with respect to all wavelength perturbations. The Carreau model has been chosen for the modeling of the rheology of a shear-thinning fluid, owing to its capability to describe properly the constant viscosity limits (Newtonian behavior) at low and high shear rates. The results are presented in the form of stability boundaries on flow pattern maps (with the phases' superficial velo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…(2017), Picchi et al. (2018), Etrati & Frigaard (2018 b ) and de Bertodano et al. (2017), driven partly by the widespread interest in gravity currents (which we do not review).…”
Section: Instabilitiesmentioning
confidence: 94%
“…(2017), Picchi et al. (2018), Etrati & Frigaard (2018 b ) and de Bertodano et al. (2017), driven partly by the widespread interest in gravity currents (which we do not review).…”
Section: Instabilitiesmentioning
confidence: 94%
“…In upward and downward inclined flows, multiple configurations may exist for fixed operational conditions (Barnea & Taitel 1992;Ullmann et al 2003b;Thibault, Munoz & Liné 2015;Picchi & Poesio 2016;Goldstein, Ullmann & Brauner 2017;Picchi et al 2017Picchi et al , 2018aPicchi, Ullmann & Brauner 2018b). For given fluids flow rates, there exist multiple steady-state solutions that differ in the volume fractions, velocity profiles and the pressure drop, but share the same flux.…”
Section: Implications For Persistently Active Volcanoesmentioning
confidence: 99%
“…It is shown that the transition from the non‐Newtonian phase b to the Newtonian phase a is captured with great accuracy, both for shear‐thinning (Figure A,B) as well as for shear‐thickening phenomena (Figure C,D). It should be noted that the shear‐thinning power‐law model has been recently found to be unrepresentative of realistic phenomena . However, it is still useful for the mathematical validation of the proposed methodology as shown in this section.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the above solution can be easily generalized to Bingham and power‐law models, by setting τ Y =0 Pa and N =1, respectively. Also to be noted that other validation cases for Newtonian/non‐Newtonian interactions can be found in the literature …”
Section: Resultsmentioning
confidence: 99%